RANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB - Reny Reny; Ahmad Taufik (Infotech: Journal of Technology Information, 2025)
The development of information technology encourages educational institutions to adopt digital systems to improve service efficiency, including in library management. SMK Wiyata Satya Jakarta still uses a manual system for the process of borrowing and returning books, member data collection, searching collections, and preparing reports, which causes inefficiency and is prone to errors. The purpose of this study is to analyze and design a web-based library information system that can overcome these problems and improve service effectiveness. This study uses the System Development Life Cycle (SDLC) waterfall model, through the stages of planning, analysis, design, implementation, and testing. The resulting system has features such as member data management, book catalogs, automatic borrowing and returning processes, fine calculations, and structured report generation. The implementation results show that the system is able to speed up the service process and minimize recording errors. The conclusion of this study is that the web-based library information system can improve operational efficiency, data accuracy, and service quality at the SMK Wiyata Satya Jakarta library.